Turning to the Heavens and the Earth : Theological Reflections on a Cosmological Conversion: Essays in Honor of Elizabeth A. Johnson - Brumbaugh, Julia; Johnson, Elizabeth A., 1941- (Book collections on Project MUSE., 2016)
The Earth needs our attention--the best of our intellectual, ethical, and spiritual wisdom and action. In this collection, written in honor of Elizabeth A. Johnson, scholars from the United States and around the world contribute their insights on how theology today can and must turn to the world in new ways in light of contemporary science and our ecological crisis. The essays in this collection advance theological visions for the human task of healing our destructive relationship with the earth and envision hope for our planet's future. (Publisher).